ГРАЖДАНСКОЕ ОБЩЕСТВО В РЕСПУБЛИКЕ МОЛДОВА: НА СТРАЖЕ ПРАВ И СВОБОД ГРАЖДАН - Миронова, Светлана, Боршевский Андрей (SUPREMANCE OF LAW, 2017)
The civil society of Moldova is in process of transition to strong institutional presence in national and local development. The civil society organizations are more often approved as authorized partners of public authorities and business, both at national and local level. The defining factors here are professionalism, openess, and active participation of the civil society organizations of different profiles in finding a solution for the problems rising in the state, on one hand, and need of implimentation of european standards, which assume active involvement of the civil society in the process of decision-making - on the other.